Śródoperacyjny krwotok naczyniówkowy u pacjenta z zespołem Rendu–Oslera - Szaflik, Jerzy; Kamińska, Anna; Zaraś, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The authors describe a 79-year-old man with Osler-Rendu-Weber syndrome, who developed intraoperative choroidal hemorrhage in left eye. During phacoemulsification under local anesthesia, shallowing of the anterior chamber was observed. Acetazolamide was administered and peribulbar block performed. Phacoemulsifikation was continued and intraocular lens implanted. Five months postoperatively resolution of the choroidal hemorrhage was observed. Best corrected visual acuity was 0.5. Patient developed retinal embolism in his right eye 16 years earlier. Conclusions: 1 Choroidal hemorrhage may occur more commonly in patients with Osler-Rendu-Weber syndrome. Recognition of this possible association and institution of appropriate intraoperative precautions may facilitate a good visual outcome. 2 Paradoxical embolization (stroke, retinal embolism) is the most serious consequence of hereditary hemorrhagic teleangiectasia.